Mrs The Content Validity of the Anxiety Scale Using Aiken’s V Approach - Yatny Mariam Lestari; Leni Anjani; Hermansyah Hermansyah; Retno Dwiyanti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Anxiety is one of the most common mental disorders experienced by individuals across various populations. The availability of anxiety measurement instruments with strong content validity in the context of the general population in Indonesia remains limited. This study aims to examine the content validity of an anxiety scale using the Aiken’s V approach. The scale consists of 30 items covering four main dimensions: cognitive, affective, physiological, and behavioral. Content validity assessment was conducted by four expert panelists. The analytical technique used was Aiken’s V content validity coefficient, with a score range of 0 to 1. The results indicate that all 30 items have V values ranging from 0.813 to 1.00. All items (100%) obtained V values greater than 0.80, indicating very high validity. The average V value across all items is 0.94. Therefore, the anxiety scale is considered to have excellent content validity based on expert judgment. The implication of this study is that the instrument can be used for the early identification of anxiety in the general population in Indonesia.